2018
DOI: 10.1002/jcb.27586
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of serum DRAM1 mRNA, ARSA mRNA, hsa‐miR‐2053 and lncRNA‐RP1‐86D1.3 axis expression in malignant pleural mesothelioma

Abstract: Aim and Background: Malignant pleural mesothelioma (MPM) is a lethal cancer mainly caused by chronic exposure of asbestos. In this pilot study, we aimed to assess the expression of serum RNA-based biomarker panel exploring their clinical utility as diagnostic and prognostic biomarkers for MPM. Methods: We have selected an MPM-specific RNA-based biomarker panel through bioinformatics analysis based on the integration of DNA damage regulated autophagy modulator 1 (DRAM1) and arylsulfatase A (ARSA) gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
(66 reference statements)
0
22
0
Order By: Relevance
“…In this study, the in silico analysis of the lncRNA expression using pleural mesothelioma and normal human pleura revealed 40 altered lncRNAs. Notably, RP1-86D1.3 [7] was not identified as differently expressed lncRNA. Additionally, Wright et al detected 33 lncRNAs differentially expressed in mesothelioma cell lines compared to MeT-5A [23], but only NEAT1 was identified in both studies.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In this study, the in silico analysis of the lncRNA expression using pleural mesothelioma and normal human pleura revealed 40 altered lncRNAs. Notably, RP1-86D1.3 [7] was not identified as differently expressed lncRNA. Additionally, Wright et al detected 33 lncRNAs differentially expressed in mesothelioma cell lines compared to MeT-5A [23], but only NEAT1 was identified in both studies.…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, it is known that earlier detection of cancer can improve survival, at least for some cancer types [44]. Thus, for early diagnosis it will also be necessary to validate GAS5 as well as the previously identified RP1-86D1.3 [7] in a prospective study regarding their potential to detect mesothelioma in prediagnostic plasma samples and to complement calretinin and mesothelin. This validation procedure is an obligatory step to select appropriate candidate markers for early detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DRAM1 (DNA damage regulated autophagy modulator 1) is an encoded lysosomal membrane protein that induces autophagy by regulation of p62. The mRNA expression of DRAM1 was positive in malignant pleural mesothelioma patient and may play an important role in tumorigenesis and progression . Furthermore, RAB24 is an atypical RAB protein which is necessary for basal autophagy.…”
Section: Discussionmentioning
confidence: 95%
“…Taking into account the limitations mentioned above, many authors (74,83,85,94,102) suggested to explore together markers of different origin to overcome the poor sensitivity and specificity of single markers. These studies combine proteins (e.g., mesothelin, fibulin, and osteopontin concentration) and different epigenetic biomarkers, including DNA methylation, expression of miRNA, and also expression of long-noncoding RNAs (lncRNAs), which are non-coding RNAs mostly involved in transcriptional regulation (103).…”
Section: Combination Of Circulating Molecular Biomarkersmentioning
confidence: 99%